Análisis musical con fines interpretativos de la obra Zapateado Ecuatoriano op. 153 del compositor Rafael Ramos Albuja y su aporte al estudio del oboe. - Barrazueta Cuenca, Michael Oswaldo (2022)
The cultural and musical diversity is an offspring present in Latin America, with European and African influences. In Ecuador, there is evidence of musical vestiges mainly Spanish by the colonizing process, germinating hybridizations as the zapateo or zapateado, creating an interest of performers and composers in the execution and creation of this music. Therefore, in the present research work we propose the realization of a musical analysis to be performed correctly the work Zapateado Ecuatoriano Op. 153, by the composer Rafael Ramos Albuja, which allows the adaptation of this work to the oboe facilitating its study. To make this project feasible, the general objective was to describe the contribution of the musical analysis with interpretative purposes of the work Zapateado Ecuatoriano Op. 153, by the composer Rafael Ramos Albuja in the study of the oboe, which, it was developed from a quantitative perspective, of non-experimental type, that is to say, variables were not used for empirical effects, rather the information obtained was contrasted from an objective approach. In addition, with a population of twelve oboists of the different Symphony Orchestras of Ecuador, a survey was applied, obtaining relevant information about the musical genre zapateado, as well as its execution and the study of this instrument. The activities related to the present project consisted in compiling diverse information, such as: bibliographic review, scientific articles and thesis works, which allowed to know the context around the musical genre called zapateado, as well as, it contributed to the identification of the contribution of the composer Rafael Ramos Albuja, through his composition Zapateado Ecuatoriano in the interpretative development of the oboe. For the musical analysis, the schekerian methodology was used, where analytical musical diminutions were extracted, which allowed the identification of a global context of the composition with respect to his melodic and harmonic structure. Also, taking into consideration this musical analysis, an adaptation was developed for the musical instrument oboe, and from this, an explanatory video on the instrument's techniques was elaborated. It is concluded that, the interpretation of Ecuadorian rhythms such as the ecuadorian zapateado, is developed without an informed criterion of this music, mostly because of the scarce information, therefore the instrumentalists do not have the necessary techniques for the study of the oboe. Therefore, its analysis becomes an effective tool for his understanding. It is recommended to oboist trainers to teach students the habit of performing the musical analysis of the compositions to be interpreted in order to understand the nature of the composition and the composer's intentionality. Keywords: cultural diversity, musical analysis, schekerian methodology